AKTUALISASI NILAI KHALIFAH DALAM AL-QURAN - Agung Kurniawan (Al-Dirayah, 2018)
This paper discusses efforts to actualize the values of the Caliphate according to the Qur'an. Humans as rulers and regulators of life on earth (Al-Baqarah: 30). At least there are three elements that are interconnected between humans and the environment, first is humans as caliphs. The Caliph is a servant of Allah who obtains a mandate as implementer, regulator, policy maker and establishes laws according to the will of Allah and the aspirations of those who pledge him as caliphs, second, is the earth. Earth or regions are places to do the Caliphate. So that, a caliph must have knowledge to manage object with their power, third is the relationship between the Almighty and the territory and its relationship with the Almighty (Allah) as a mustakhlilf. Empirical experience shows that the main factors that make an important contribution in a good environmental management effort are the leadership factors inherent in their leaders. The ability to refrain from damaging the environment and realizing the sustainability of development. The role of humans is actually as a creature choosen by God not just as a ruler on earth. But also its role to prosper the earth. The contextualization of the role of the caliphate is actually the first step in maintaining the environment which is increasingly damaged, and even brings total destruction to the world.